(3GddBdF GdSfOSjI aj GdaVGFd GdSfhSjIs - (3eMeO Hf YeQ Hf EHQGgje GdedGdj GdJdeSGfjs ((3YHOGdeLjO Hf Ydj GdMSfj GdedGdj s)
(3ChdgG (B:s
(3hHYO deG bOQ Gddg HdOI eQGcT hSgd dj Gdhbha Ydi LedI cJH ZQGFH aef LedI eG CJhG Hg cJGH cHjQ s
(3BNQgG (B:s
(3jbhd oeNJUQg (B: (3gPG BNQ eGbUOJg ef GNJUGQ eG CQOJg BNQ OYhGfG Cf GdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B107 - (3U(B132s
(3gPg GdfSNI ef fSNI JGQjNgG(B1066 (3g` ef NW GdYdGeI CMeO GdeZQHj GdJdeSGfj efShNI ef fSNI GdeDda HNWgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs